Colistin Resistance in Escherichia coli and Salmonella enterica Strains Isolated from Swine in Brazil. (22nd August 2012) - Morales, Adriano Savoia; Fragoso de Araújo, Juliana; de Moura Gomes, Vasco Túlio; Reis Costa, Adrienny Trindade; Prazeres Rodrigues, Dália dos; Porfida Ferreira, Thais Sebastiana; de Lima Filsner, Pedro Henrique Nogueira; Felizardo, Maria Roberta; Micke Moreno, Andrea
Abstract : Reports about acquired resistance to colistin in different bacteria species are increasing, including E. coli of animal origin, but reports of resistance in wild S. enterica of different serotypes from swine are not found in the literature. Results obtained with one hundred and twenty-six E. coli strains from diseased swine and one hundred and twenty-four S. enterica strains from diseased and carrier swine showed a frequency of 6.3% and 21% of colistin-resistant strains, respectively. When comparing the disk diffusion test with the agar dilution test to evaluate the strains, it was confirmed that the disk diffusion test is not recommended to evaluate colistin resistance as described previously. The colistin MIC 90 and MIC 50 values obtained to E. coli were 0.25 μ g/mL and 0.5 μ g/mL, the MIC 90 and MIC 50 to S. enterica were 1 μ g/mL and 8 μ g/mL. Considering the importance of colistin in control of nosocomial human infections with Gram-negative multiresistant bacteria, and the large use of this drug in animal production, the colistin resistance prevalence in enterobacteriaceae of animal origin must be monitored more closely.